What happened on Blackstone Avenue? Exorcising coase theorem mythology - Steven G. Medema (Duke University, Center for the History of Political Economy (CHOPE), 2021)
The present paper revisits the path by which Coase came to set down the result now generally known as the Coase theorem in his 1960 article. I draw on both the published record and archival resources in an effort to clear away some of the mist and, as it will emerge, dispel some of the mythology. As good as the traditional story is - thanks in no small part to Stigler's hyperbole - the reality is far more interesting, both for what it tells us about Coase's result and for our understanding of the messy process behind how it came to be. For as we shall see, Coase set out at least three versions of his result, two of them assuredly incorrect, in 1959-60 and had at best a faint sense for the implications of transaction costs for his conclusion - something which he was only put on to by others to whom he showed the original draft of his 1959 article. And as for that fateful evening during which he "converted" the Chicagoans to his point of view, we shall see both that the extent of the conversion necessary was far less than the traditional story suggests and that it is not at all clear what it was that the Chicagoans believed at the end of the evening, Coase's 1960 argument notwithstanding.
Keywords: B21; B31; H23; K00; L1; Q50; 330; Ronald Coase; transaction costs; Coase theorem; externalities